As fronteiras do acesso à justiça - Montes, Priscila Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The present work aims to diagnose the reasons why the right to judicial access is diminished to those in structural poverty situation. In this way, it departs from the frontiers, i.e., from the limits which separate two universes: one is conceived to orientate order and knowledge; the other one to be marginalized immediately. It was decided by the side occupied by the oppressed individuals, represented by the colonized societies in a global scope and the environment where those oppressed live in, exiled from human conditions in a local community. Initially guided by the Extreme Poverty and Human Rights Commission report by the UNDP, we point out eight possible judicial access frontiers. Yet, there are clues that those would be only detachments from a larger frontier, which could only be analyzed by going back in past and seeking the comprehension of how factors of internal and external domination act towards the consolidation of underdevelopment, dependent capitalism, competitive order and, subsequently, for the social classes disparity. It is know that Brazil has singularities that do not permit the immediate adoption of theories and solutions which are effective abroad. Finally, this work intends to analyze how these factors act on the judicial access problematic - which creates then a barrier that prevents the democratic order and deny the right to citizenship to many individuals

O presente trabalho tem por objetivo diagnosticar o porquê do direito ao acesso à justiça ser mitigado àqueles que estão em situação de pobreza estrutural. Para tanto, parte das fronteiras, ou seja, de limites que separam dois universos: um concebido para orientar ordem e conhecimento; e outro para ser marginalizado de pronto. Opta-se pelo lado habitado pelos oprimidos, representado pelas sociedades colonizadas em um âmbito global e o ambiente em que vive os exilados da condição humana em uma seara local. Orientando-se inicialmente pelo relatório da Comissão de Extrema Pobreza e Direitos Humanos, do PNUD, extrai-se oito possíveis fronteiras do acesso à justiça. Há indícios, porém, que estas seriam apenas pequenos desmembramentos de uma fronteira maior, a qual só poderia ser desvendada pela volta ao passado, buscando a compreensão de como fatores de dominação interna e externa agem para a consolidação do subdesenvolvimento, capitalismo dependente, ordem competitiva e, consequentemente, para a assimetria de classes sociais. Entende-se que o Brasil possui peculiaridades que não permitem a pronta adoção de teorias e soluções que em solo estrangeiro são efetivos. Pretende-se analisar, por fim, como esses fatores atuam na temática do acesso à justiça, constituindo, assim, uma fronteira a impedir a ordem democrática e possibilitar a negação do direito de cidadania à inúmeros sujeitos
Keywords: Direito; Direitos humanos; Cidadania; Fronteiras; Acesso à justiça; Direitos sociais; Law